Tindak Kejahatan Perdagangan Manusia Di Dunia Sebagai Bentuk Pelanggaran Hak Asasi Manusia Di Era Globalisasi - Ahmad Sahhil Dany Maulana; Andi Aina Ilmih (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Human trafficking or often called human trafficking is a type of transnational crime involving violations of human rights (HAM). This is related to violations of the most fundamental human rights, namely the right to freedom, a better life, prosperity and human rights as creatures with dignity. The government's protection of its citizens is still relatively ineffective, because there are still many unknown victims of exploitation. The increasingly developing era of globalization makes it easier for citizens throughout the world to carry out human trafficking considering that various information is easy to obtain. Human trafficking is usually carried out using fraudulent methods such as promises of something, for example marriage, work abroad with a large salary, and so on. So human trafficking is an important issue that needs to be discussed and addressed as best as possible so that citizens can obtain their rights as human beings with dignity. A nation can grow as a great nation if the people within it do not fall into criminal acts such as human trafficking which is a heinous crime to commit. Humans are not goods that can be bought and sold and can be exploited arbitrarily..